2011
DOI: 10.1159/000327600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recovery and Anesthetic Gas Consumption Using Remifentanil Combined with Low-Flow Sevoflurane Anesthesia in Tympanoplasty

Abstract: Background: The aim of this study was to compare the effects of low-flow sevoflurane and low-flow sevoflurane supplemented with remifentanil anesthesia on the recovery time, consumption amount of the anesthetic drugs and hemodynamic differences. Materials and Methods: A prospective, randomized and double-blinded study with 50 patients was designed. Following intubation, group S received sevoflurane 1.8 vol%, oxygen, nitrous oxide at 4 l · min–1 and normal saline continuous infusion; group SR receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Similarly, Kim et al [7] in a study of 40 females undergoing gynecological surgery with entropy monitored general anesthesia, demonstrated that the end-tidal sevoflurane concentration as well as the total volatile gas consumption had been reduced by continuous intraoperative remifentanil infusion. We agree with those authors [7,36] in the context that reducing the consumption of the inhalational anesthetics without compromising both the clinical outcome and the patient satisfaction is highly desirable in order to facilitate earlier recovery from general anesthesia and to minimize the environmental pollution and the economic waste. In the present study, we used the spectral entropy monitoring to titrate the sevoflurane concentration to the desirable depth of anesthesia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, Kim et al [7] in a study of 40 females undergoing gynecological surgery with entropy monitored general anesthesia, demonstrated that the end-tidal sevoflurane concentration as well as the total volatile gas consumption had been reduced by continuous intraoperative remifentanil infusion. We agree with those authors [7,36] in the context that reducing the consumption of the inhalational anesthetics without compromising both the clinical outcome and the patient satisfaction is highly desirable in order to facilitate earlier recovery from general anesthesia and to minimize the environmental pollution and the economic waste. In the present study, we used the spectral entropy monitoring to titrate the sevoflurane concentration to the desirable depth of anesthesia.…”
Section: Discussionsupporting
confidence: 84%
“…Sert and his colleagues [36] concluded that the use of low flow sevoflurane anesthesia combined with continuous intraoperative remifentanil infusion during tympanoplasty resulted in a faster early recovery and decreased sevoflurane consumption. Similarly, Kim et al [7] in a study of 40 females undergoing gynecological surgery with entropy monitored general anesthesia, demonstrated that the end-tidal sevoflurane concentration as well as the total volatile gas consumption had been reduced by continuous intraoperative remifentanil infusion.…”
Section: Discussionmentioning
confidence: 99%